A randomized controlled trial comparing controlled reoxygenation and standard cardiopulmonary bypass in paediatric cardiac surgery. (30th October 2020) - Caputo, Massimo; Scott, Lauren J; Deave, Toity; Dabner, Lucy; Parry, Andrew; Angelini, Gianni D; Sheehan, Karen; Stoica, Serban; Ellis, Lucy; Harris, Rosie; Rogers, Chris A
Abstract: OBJECTIVES: Controlled reoxygenation on starting cardiopulmonary bypass (CPB) rather than hyperoxic CPB may confer clinical advantages during surgery for congenital cyanotic heart disease. METHODS: A single-centre, randomized controlled trial was carried out to compare the effectiveness of controlled reoxygenation (normoxia) versus hyperoxic CPB in children with congenital cyanotic heart disease undergoing open-heart surgery (Oxic-2). The co-primary clinical outcomes were duration of inotropic support, intubation time and postoperative intensive care unit (ICU) and hospital stay. Analysis of the primary outcomes included data from a previous trial (Oxic-1) conducted to the same protocol. RESULTS: Ninety participants were recruited to Oxic-2 and 79 were recruited to the previous Oxic-1 trial. There were no significant differences between the groups for any of the co-primary outcomes: inotrope duration geometric mean ratio (normoxia/hyperoxic) 0.97, 95% confidence interval (CI) (0.69–1.37), P -value = 0.87; intubation time hazard ratio (HR) 1.03, 95% CI (0.74–1.42), P -value = 0.87; postoperative ICU stay HR 1.14 95% CI (0.77–1.67), P -value = 0.52, hospital stay HR 0.90, 95% CI (0.65–1.25), P -value = 0.53. Lower oxygen levels were successfully achieved during the operative period in the normoxic group. Serum creatinine levels were lower in the normoxic group at day 2, but not on days 1, 3–5. Childhood developmental outcomes were similar. In the year following surgery, 85 serious adverse events were reported (51 normoxic group and 34 hyperoxic group). CONCLUSIONS: Controlled reoxygenation (normoxic) CPB is safe but with no evidence of a clinical advantage over hyperoxic CPB. Clinical trial registration number: Current Controlled Trials—ISRCTN81773762. Abstract : Cyanotic children undergoing open-heart surgery are particularly susceptible to reoxygenation injury, arising from the intraoperative reintroduction of high molecular oxygen levels on starting cardiopulmonary bypass (CPB), prior to the ischaemic cardioplegic arrest [1, 2].